Torajan’s Pray through Carving in Rampanan Kapa’ Semiotics Perspective) - Sirande, Normalia; Judith Ratu Tandi Arrang; Linerda Tulaktondok (Universitas Cokroaminoto Palopo, 2024)
Toraja is one of the tribes in Indonesia that gets a legacy of carving motifs as a means of teaching for posterity of their ancestors. This research aimed to find the types of carving motifs used in the decoration of traditional wedding events in Toraja. This research used qualitative research methods of ethnographic type and purpossive sampling techniques. The results of this study found at least fifteen types of carving motifs that have been used in decorations for traditional wedding events, Rampanan Kapa’, by Torajan. The carving motifs are Pa'tukku pare, Pa' lolo tabang, Pa' bungkang danau, Pa' tangke lumu', Pa' erong, Pa' Bombo wai, pa' bare' allo, Pa' batang lau, Pa' kapu' baka, Passungkalla', Passekong kandaure, Pa' tedong, Pa' bulu londong, Passora, and Pa' poya mundan. The fifteen carving motifs contain prayers and hopes from all those who attended the Kapa' Rampanan event for both brides.